Impact of exposure to opioids in pregnancy on offspring developmental outcomes in the preschool years: an umbrella review - Louise Marryat; Thomas Hughes; James Boardman; Alison McFadden; Senga Robertson; Anne Whittaker (BMJ Paediatrics Open)
Background Early child development sets the course for optimal outcomes across life. Increasing numbers of children worldwide are exposed to opioids in pregnancy and frequently live in environments associated with adverse developmental outcomes. Although multiple systematic reviews have been published in this area, they use different exposures and different types of outcomes. This umbrella review aims to bring together these systematic reviews to provide a comprehensive overview of the evidence around the association between prenatal opioid exposure and preschool developmental outcomes.Methods PubMed, MedLine, PsycInfo and Google Scholar were searched up to July 2024. Eligible studies were systematic reviews, meta-analyses or scoping reviews exploring prenatal opioid exposure (illicit opioids and prescribed treatments for opioid dependence) and developmental outcomes up to age 5. Reviews were screened by two authors. Quality assessment was undertaken using the Joanna Briggs Institute checklist for umbrella reviews. Degree of overlap was examined. Due to heterogeneity within the sample, no meta-analyses were undertaken and results were synthesised narratively.Results 11 reviews were included containing 478 individual papers. The overlap was slight (corrected cover area=5%). Developmental outcomes associated with prenatal opioid exposure included visual function, motor skills, externalising problems and language difficulties. No conclusive evidence was available for cognitive development or internalising symptoms. In cognitive, and motor, skills, findings differed by age, with later preschool findings being weaker. Authors frequently highlighted issues with poor quality research in the original studies, including small sample sizes and lack of controlling for confounding.Conclusions Multiple areas of child development were associated with prenatal opioid exposure; however, evidence was weak. Robust research, with larger sample sizes and adequate accounting for confounding, is needed to provide accurate information for women of childbearing age and practitioners to guide policy and ensure that appropriate funding, support and follow-up are in place.PROSPERO registration number CRD42022307992.